UPAYA ORANGTUA DALAM MENUMBUHKAN SIKAP KEPEDULIAN SOSIAL ANAK USIA DINI TERHADAP KORBAN BENCANA ALAM - Neng Nurcahyati Sinulingga; Resti Oktriani Sinulingga (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
Abstract. Children are the most valuable entrusted which of course has been given by Allah SWT, to his chosen servants and made him parents who will be able to guide their offspring to become brilliant Islamic generations. One way to develop a child's personality in making him an Islamic generation is by educating him to be more sensitive in terms of social care for fellow human beings. This research belongs to the type of qualitative research and the method used in this research is a literature review study type method, and the entire data collection uses references to books and journals that are currently relevant. Furthermore, the results of the research in this article have shown that: (1) the basic concept of social care in early childhood regarding natural disasters according to an Islamic perspective, of course, provides learning that social care is a worship which of course will surely be rewarded by Allah (2) Forms the caring attitude of early childhood in their environment can be seen as carrying out mutual assistance activities both in the family and surrounding environment, habituation of activities carried out every day, as well as social care for others, (3) Efforts made by parents in fostering social awareness in early childhood in helping victims of natural disasters, namely by making several efforts which include: (1) instilling a social care spirit in children from an early age, (2) involving children in social activities, (3) instilling compassion for one another, etc.